Alice in Wonderland Syndrome Asociated with Topiramate for Adolescent Migraine Prevention - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Neuroscientists at the University Medical Centre Hamburg, Germany, report the case of a 17-year-old girl with migraine without aura who developed an intermittent "Alice in Wonderland Syndrome" associated with prophylactic treatment of migraine headaches with topiramate.